The Use of Problem-Based Learning (PBL) and Inquiry Models to Develop Critical Thinking Skills and Improve Cognitive Learning Outcomes of Students at SMP Negeri 13 Lebong - Poppy Lariski; Siti Darwa Suryani; Kashardi Kashardi (International Journal of Educational Research, 2025)
This study aims to determine the effect of Problem Based Learning (PBL) and Inquiry learning models on students’critical thinking skills and cognitive learning outcomes on the topic of the human respiratory system. This research used a quasi-experimental design with a Non-Equivalent Pretest-Posttest Control Group Design. The research subjects were three eighth-grade classes at SMP Negeri 13 Lebong, consisting of two experimental classes taught using the PBL and Inquiry models and one control class using conventional methods. The research instruments included essay tests to measure critical thinking and multiple-choice tests to assess cognitive learning outcomes. Data were analyzed using ANOVA and LSD tests. The results showed significant differences among the three groups. The PBL model produced the highest improvement in both variables, followed by Inquiry, and lastly the control group. Therefore, PBL is proven to be the most Effective model inimproving students' critical thinking and cognitive learning outcomes in science education.